2018
DOI: 10.1093/abm/kax035
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity and Alzheimer’s Disease (PAAD) Study: Cognitive outcomes

Abstract: Future experimental studies are needed to confirm that PA causes improvements to cognitive performance in older cognitively normal adults with a FHxAD and that these improvements are equivalent for cognitively normal APOE ɛ4 carriers and noncarriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
13
0
3
Order By: Relevance
“…The risk of developing AD should be considered from early ages, to avoid risk factors, and for the elderly, it is important to improve treatments by adopting a healthier lifestyle and dietary changes; in order to strengthen prevention (10) There is a lot of obesity type diabetes, that is closely related to the factors that promote the evolution towards AD (lack of physical activity, stress, lack of socialization-witch are the main preventive elements in AD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of developing AD should be considered from early ages, to avoid risk factors, and for the elderly, it is important to improve treatments by adopting a healthier lifestyle and dietary changes; in order to strengthen prevention (10) There is a lot of obesity type diabetes, that is closely related to the factors that promote the evolution towards AD (lack of physical activity, stress, lack of socialization-witch are the main preventive elements in AD).…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, physical activities that have additional components of social and cognitive stimulation are considered to be the most effective. (7 ,8, 9) AD is a very important health problem that requires screening to monitor cardiovascular risk factors, so that prevention strategies can be implemented in order to minimize the risk of its development (10).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research has shown that a low level of physical activity is associated with a higher risk of cognitive decline, particularly among APOE ε4 carriers (Schuit et al 2001). On the other hand, researchers from the University of North Carolina recently reported an improvement in memory function after an 8-month physical activity intervention irrespective of APOE ɛ4 carrier status (Etnier et al 2018). However, interestingly, we observed in our data that engaging in midlife activity regardless of intensity level was associated with significantly less decrease in memory function only among APOE ε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…One such marker is the apolipoprotein E ( APOE ) ε4 allele, which is a well-known genetic risk factor for Alzheimer’s disease (Corder et al 1993; Roses 1996; Saunders et al 1993). A growing body of research has implicated that the association between physical activity and cognitive function may differ by APOE ε4 carrier status (Etnier et al 2018; Rovio et al 2005; Schuit et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting but inconsistent finding within published exercise trials is the potentially differential effect based on genetic risk for AD (APOE) [123,124]. Although results have been mixed, several studies have demonstrated that the beneficial effects of aerobic training may be greater among individuals with greater AD genetic risk, [123] although others have failed to replicate these subgroup differences [125,126]. Taken together, these findings suggest that being physically active in middle-age is likely protective against future ADRD, although there is wide individual variation across individuals that remains to be understood, as discussed in later sections below.…”
Section: Physical Activitymentioning
confidence: 99%